2019
DOI: 10.3390/pathogens8020049
|View full text |Cite
|
Sign up to set email alerts
|

Macrocolony of NDM-1 Producing Enterobacter hormaechei subsp. oharae Generates Subpopulations with Different Features Regarding the Response of Antimicrobial Agents and Biofilm Formation

Abstract: Enterobacter cloacae complex has been increasingly recognized as a nosocomial pathogen representing the third major Enterobacteriaceae species involved with infections. This study aims to evaluate virulence and antimicrobial susceptibility of subpopulations generated from macrocolonies of NDM-1 producing Enterobacter hormaechei clinical isolates. Biofilm was quantified using crystal violet method and fimbrial genes were investigated by PCR. Susceptibility of antimicrobials, alone and combined, was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…blood, urine, feces, and body fluids) 33 . On the other hand, studying the biofilm production of 9 strains of E. hormaechei from clinical origin reported that they formed a moderate biofilm 34 . Other studies have been evidenced the capability of K. pneumoniae to produce weak and moderate biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…blood, urine, feces, and body fluids) 33 . On the other hand, studying the biofilm production of 9 strains of E. hormaechei from clinical origin reported that they formed a moderate biofilm 34 . Other studies have been evidenced the capability of K. pneumoniae to produce weak and moderate biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the differences in biofilm formation ability among different species of ECC, biofilm formation assays were performed in a 96-well polystyrene microtiter plate, as previously described with some modifications ( Brust et al, 2019 ). Briefly, the isolates were grown overnight in Luria–Bertani (LB) broth at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In order to investigate the differences in virulence genes among various species of ECC, the genome DNA of all 130 ECC strains was extracted using the Biospin Bacterial Genomic DNA Extraction kit (Bioflux, Tokyo, Japan) according to the manufacturer’s instructions and served as templates for subsequent analysis. Virulence genes, including fimA (type 1 fimbriae gene) ( Brust et al, 2019 ), mrkD (type 3 fimbriae gene) ( Compain et al, 2014 ), csgD (curli gene) ( Brust et al, 2019 ), papC and papD (P pili genes) ( Brust et al, 2019 ), fyuA ( Yersinia siderophore receptor gene) ( Johnson et al, 2015 ), iroNec (salmochelin siderophore receptor gene) ( Johnson et al, 2015 ), entB (enterobactin gene) ( May and Okabe, 2011 ), and ybtS (yersiniabactin gene) ( El Fertas-Aissani et al, 2013 ), were identified by PCR. The primers of all genes for PCR are listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…E. cloacae is an important opportunistic pathogen with complex genetic elements that can produce a variety of antibiotic hydrolases, and current studies have shown that carbapenemase, especially NDM-1, is the main resistance mechanism of carbapenem-resistant E. cloacae (CR-ECL) [1,2]. E. cloacae infect hosts and cause disease through various mechanisms, such as colonization, invasion, evasion of the immune response, and release of toxins [3,4], and its pathogenic process is closely related to various virulence factors such as fimbriae, siderophore, toxin secretion system, biofilm, efflux pump, virulence island and lipopolysaccharide [5][6][7]. E. cloacae contains abundant plasmid and chromosomal genomes and has easy access to multiple mobile genetic elements containing antimicrobial resistance genes and virulence genes, both of which play an important role in the evolution of bacteria mainly through gene-level transfer and are interrelated [3].…”
Section: Introductionmentioning
confidence: 99%